High-Dose Intravenous Immunoglobulins in the Treatment of Severe Acute Viral Pneumonia: The Known Mechanisms and Clinical Effects - Liu, Xiaosheng; Cao, Wei; Li, Taisheng (Frontiers in Immunology, 2020)
The current outbreak of viral pneumonia, caused by novel coronavirus SARS-CoV-2, is a focus of worldwide attention. The WHO declared the COVID-19 outbreak a pandemic event on Mar 12, 2020, and the number of confirmed cases is still on the rise worldwide. While most infected individuals experience only mild symptoms or may even be asymptomatic, some patients rapidly progress to severe acute respiratory failure with substantial mortality, which makes it imperative to develop an efficient treatment for severe SARS-CoV-2 pneumonia alongside supportive care. So far, the optimal treatment strategy for severe COVID-19 remains unknown. Intravenous immunoglobulin (IVIg) is a blood product pooled from healthy donors with high concentrations of immunoglobulin G (IgG) and has been used in patients with autoimmune and inflammatory diseases for more than 30 years. In this review, we aim to highlight the known mechanisms of immunomodulatory effects of high-dose IVIg therapy, the immunopathological hypothesis of viral pneumonia, the clinical evidence of IVIg therapy in viral pneumonia, and we make cautious therapeutic inferences about high-dose IVIg therapy in treating severe COVID-19. These inferences may provide relevant and useful insights in order to aid treatment for COVID-19.